2020
DOI: 10.1136/emermed-2020-209887
|View full text |Cite
|
Sign up to set email alerts
|

Evidence base for point-of-care ultrasound (POCUS) for diagnosis of skull fractures in children: a systematic review and meta-analysis

Abstract: BackgroundBlunt head trauma is a common presentation to emergency departments (EDs). Identifying skull fractures in children is important as they are known factor of risk for traumatic brain injury (TBI). Currently, CT is the reference standard for diagnosing skull fractures and TBIs in children. Identifying skull fractures with point-of-care ultrasound (POCUS) may help risk-stratify children for TBI following blunt trauma. The purpose of this study is to evaluate the sensitivity, specificity, positive predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
(109 reference statements)
1
16
0
1
Order By: Relevance
“…Both included prospective studies that compared POCUS results with CT scan findings (reference standard). Both meta-analyses, although slightly different in the methods and in the number of studies included [six studies in Gordon et al ( 39 ) and seven in Alexandridis et al ( 38 )] found a pooled sensitivity of 91% and a pooled specificity of 96%, confirming the accuracy of POCUS in detecting skull fractures. Overall, the largest meta-analysis analyzed 925 patients, with study samples ranging from 21 to 538 patients and percentage of skull fractures on CT ranging from 10 to 77%.…”
Section: Point Of Care Ultrasoundmentioning
confidence: 91%
See 2 more Smart Citations
“…Both included prospective studies that compared POCUS results with CT scan findings (reference standard). Both meta-analyses, although slightly different in the methods and in the number of studies included [six studies in Gordon et al ( 39 ) and seven in Alexandridis et al ( 38 )] found a pooled sensitivity of 91% and a pooled specificity of 96%, confirming the accuracy of POCUS in detecting skull fractures. Overall, the largest meta-analysis analyzed 925 patients, with study samples ranging from 21 to 538 patients and percentage of skull fractures on CT ranging from 10 to 77%.…”
Section: Point Of Care Ultrasoundmentioning
confidence: 91%
“…In the context of pediatric MHT, this technique is particularly useful when a scalp hematoma is present and clinical signs of a palpable skull fracture may be unclear or doubtful to define the presence of an underlying depressed or complicated fracture of the skull ( 36 , 37 ). Two recent meta-analyses ( 38 , 39 ) evaluated the accuracy of skull POCUS performed by ED physicians in identifying skull fractures in children with head trauma. Both included prospective studies that compared POCUS results with CT scan findings (reference standard).…”
Section: Point Of Care Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for point of care ultrasound for the diagnosis of skull fractures in children has been recently reviewed in a systematic review and meta-analysis by Alexandridis et al [ 12 * *], who appraised 7 relevant studies. Sensitivity ranged from 67–100% and specificity from 85%-100%.…”
Section: Alternatives To Ctmentioning
confidence: 99%
“…Frequently, point of care ultrasounds are performed by the resident clinical team, with wide variability in ultrasound experience and expertise. In the meta-analysis by Alexandridis et al [ 12 * *], ultrasounds were typically performed by clinicians after a training period of 1 h. This will contribute to the reported specificity of the various studies, with operators with the most experience and training invariably attaining the most accurate diagnoses.…”
Section: Alternatives To Ctmentioning
confidence: 99%